GE_GERICHTE P/17545/2016 vom 30. November 2017 - GE Cour de justice (2017)
DROIT D'ÊTRE ENTENDU ; PRINCIPE DE L'ACCUSATION ; MENACE(DROIT PÉNAL) ; DÉPENS | CP.180; CP.34.leta; LEtr.115.al1.letb; LEtr.115.al1.letc; CPP.429